Finansy I razvitie, March 2012. (Finance and Development; Finance and Development ;, 2012)
Young people, hardest hit by the global economic downturn, are speaking out and demanding change. F and D looks at the need to urgently address the challenges facing youth and create opportunities for them. Harvard professor David Bloom lays out the scope of the problem and emphasizes the importance of listening to young people in "Youth in the Balance." "Making the Grade" looks at how to teach today's young people what they need to get jobs. IMF Deputy Managing Director, Nemat Shafik shares her take on the social and economic consequences of youth unemployment in our "Straight Talk" column. "Scarred Generation" looks at the effects the global economic crisis had on young workers in advanced economies, and we hear directly from young people across the globe in "Voices of Youth." Renminbi's rise, financial system regulation, and boosting GDP by empowering women. Also in the magazine, we examine the rise of the Chinese currency, look at the role of the credit rating agencies, discuss how to boost the empowerment of women, and present our primer on macroprudential regulation, seen as increasingly important to financial stability. People in economics - C. Fred Bergsten, American Globalist Back to basics - The multi-dimensional role of banks in our financial systems.